Across language families: Genome diversity mirrors linguistic variation within Europe. Issue 4 (8th June 2015) - Longobardi, Giuseppe; Ghirotto, Silvia; Guardiano, Cristina; Tassi, Francesca; Benazzo, Andrea; Ceolin, Andrea; Barbujani, Guido
ABSTRACT Objectives: The notion that patterns of linguistic and biological variation may cast light on each other and on population histories dates back to Darwin's times; yet, turning this intuition into a proper research program has met with serious methodological difficulties, especially affecting language comparisons. This article takes advantage of two new tools of comparative linguistics: a refined list of Indo‐European cognate words, and a novel method of language comparison estimating linguistic diversity from a universal inventory of grammatical polymorphisms, and hence enabling comparison even across different families. We corroborated the method and used it to compare patterns of linguistic and genomic variation in Europe. Materials and Methods: Two sets of linguistic distances, lexical and syntactic, were inferred from these data and compared with measures of geographic and genomic distance through a series of matrix correlation tests. Linguistic and genomic trees were also estimated and compared. A method (Treemix) was used to infer migration episodes after the main population splits. Results: We observed significant correlations between genomic and linguistic diversity, the latter inferred from data on both Indo‐European and non‐Indo‐European languages. Contrary to previous observations, on the European scale, language proved a better predictor of genomic differences than geography. Inferred episodes of genetic admixture following the main population splits found convincing correlates also in the linguistic realm. Discussion: These results pave the ground for previously unfeasible cross‐disciplinary analyses at the worldwide scale, encompassing populations of distant language families. Am J Phys Anthropol 157:630–640, 2015. © 2015 Wiley Periodicals, Inc.